A citation network analysis of career mentoring across disciplines. A roadmap for mentoring research in sport - Lefebvre, J. S.; Bloom, G. A.; Loughead, T. M. (Psychology of Sport and Exercise, 2020)
Objective: Given our limited understanding of mentoring in sport, reviewing research from other disciplines has the potential to advance knowledge in this context. Therefore, the purpose of this study was to synthesize and evaluate the mentoring literature across disciplines in order to bridge existing knowledge and to situate the mentoring in sport literature.